Hemorheological disturbances in the overtraining syndrome - Varlet-Marie, E.; Maso, F.; Lac, G.; Brun, J. F. (Clinical Hemorheology and Microcirculation, 2003)
Contemporary sports imply huge training volumes, with thus an increasing danger of overloading. The timely detection of the state of overloading in the organism as a whole or in skeletal muscles presents a difficult and complicated problem. A standardized questionnaire has been proposed by the French consensus group on overtraining of the Société Française de Médecine du Sport (SFMS) and allows the calculation of a "score" that may help to quantify the early clinical symptoms of the overtraining syndrome in sportsmen submitted to a heavy training program. We previously reported that this overtraining score is correlated with blood viscosity due to a correlation of this score with plasma viscosity and hematocrit. When subjects with a high score were compared to subjects with a lower score they appeared to have a higher blood viscosity at native (but not corrected) hematocrit, explained by higher values in both plasma viscosity and hematocrit. By contrast, there was no difference in RBC deformability and aggregation. Therefore, the early signs of overtraining in elite sportsmen are associated with a hemorheologic pattern that suggests some degree of reversal of the "autohemodilution" which characterizes fitness. In a further study we reported that the feeling of heavy legs in overtrained athletes is related to impaired hemorheology. Although well matched with controls for age and body composition, subjects with a complaint of heavy legs had higher plasma viscosity and a higher red cell aggregation as measured with laser backscattering. These findings suggest that the feeling of heavy legs in overtrained athletes are related to hemorheologic disturbances. In the light of the recent concept explaining this syndrome by a mild chronic inflammatory reaction, the investigation of hemorheology in overtraining can be a promising area for hemorheologists, providing both markers and likely pathophysiological explanations for some symptoms of this situation.